Investment Literation Improvement for Preparation of Investments for Young Investors - Linzzy Pratami Putri; Irma Christiana; Delyana Rahmawany Pulungan; Isna Ardila (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
This study aims to determine the financial literacy and investment of students and their influence on the ability of students to manage finances and the ability of students to manage assets owned to be invested. The data analysis method used in this research is the Structural Equation Model or SEM method. To see the factors that influence the ability to manage finances and the ability to manage assets, Partial Least Square (PLS) analysis is performed. This analysis is used by looking at the number of samples that are a bit of an obstacle if you want to do an analysis using factor analysis or Structural Equation Model (SEM). Thus, analysis using PLS is appropriate. The results of this study are of 5 (five) literacy variables, namely capital market literacy, type of investment instrument literacy, profit level literacy, investment literacy, and financial literacy on the ability to manage finances, only investment literacy has no significant effect, more influence significant ability to manage finances. Then from (5) five literacy variables that do not have a significant influence on the ability of students to manage assets are capital market literacy and investment literacy.